Psoriatic Arthritis and Metabolic Syndrome: Is There a Role for Disease Modifying Anti-Rheumatic Drugs? - Atzeni, Fabiola; Gerratana, Elisabetta; Francesco Masala, Ignazio; Bongiovanni, Sara; Sarzi-Puttini, Piercarlo; Rodríguez-Carrio, Javier (Frontiers in Medicine, 2021)
Although psoriatic arthritis (PsA) primarily leads to joint and skin damage, it is associated with higher prevalence of metabolic syndrome (MetS) and its components, namely hypertension, dyslipidemia, obesity and type II diabetes. Additionally, chronic inflammation is known to aggravate these cardiometabolic factors, thus explaining the enhanced cardiovascular (CV) morbidity and mortality in RA. Furthermore, emerging evidence suggest that some risk factors can fuel inflammation, thus pointing to a bidirectional crosstalk between inflammation and cardiometabolic factors. Therefore, dampening inflammation by disease-modifying anti-rheumatic drugs (DMARDs) may be thought to ameliorate MetS burden and thus, CV risk and disease severity. In fact, recommendations for PsA management emphasize the need of considering comorbidities to guide the treatment decision process. However, the existing evidence on the impact of approved DMARDs in PsA on MetS and MetS components is far from being optimal, thus representing a major challenge for the clinical setting. Although a beneficial effect of some DMARDs such as methotrexate, TNF inhibitors and some small molecules is clear, no head-to-head studies are published and no evidence is available for other therapeutic approaches such as IL-23 or IL-17 inhibitors. This narrative review summarizes the main evidence related to the effect of DMARDs on MetS outcomes in PsA patients and identify the main limitations, research needs and future perspectives in this scenario.